Evaluation of Different Thyroid Lesions with Fine Needle Aspiration Cytology and Thyroid Function Tests - Ranabhat, S; Parajuli, B; Poudel, S; Pun, G (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Swelling of the thyroid gland is a commonly encountered clinical problem in all age groups whether benign or malignant. Fine Needle Aspiration Cytology (FNAC) of the thyroid lesions along with hormonal function test helps in the proper preoperative assessment. Ultimately it changes clinical management and improves the patient outcome. Objectives: To describe the cytomorphological features of palpable thyroid nodules using fine needle aspiration cytology (FNAC) along with the assessment of thyroid hormonal status of the patient. Methods: The study was conducted in the Department of Pathology of Gandaki Medical College and Teaching hospital from January 2017 to December 2017 and included 50 patients with thyroid lesions. Cytological assessment was done using FNAC along with serological assessment of thyroid hormones. Results: In the study 50 cases of thyroid swelling were included and evaluated by cytological and hormonal analysis which comprises of 10% males and 90% females with a with a female to male ratio of 9 : 1. Maximum number of cases was seen in the age range 41 - 60 years (46%), mean age being 44.6 years. The cytological diagnosis comprised colloid goiter (58%), lymphocytic thyroiditis (16%), Hashimoto thyroiditis (10%). Thyroid hormone analysis showed 66% euthyroid, 22% hypothyroid and 12% hyperthyroid. Conclusions: The study showed that FNAC and TFT profile both are essential for the proper management of thyroid lesions. FNAC along with hormonal analysis helps in proper patient assessment and management. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 17-22